Mechanisms of e-commerce enterprises development in the context of digitalization (Nexo Revista Científica, 2021)
The article deals with the development of a mechanism for the e-commerce enterprises' extension in the context of digitalization. It is established that e-commerce enterprises should actively implement the possibility of combining offline and online channels and consider ways to improve the operational efficiency of conducting activities through the automation of commodity accounting and analytical accounting systems, the development of loyalty programs, and acquiring including through the use of contactless payment technology. It is proved that digital trade enterprises need to actively implement self-service cash registers and develop their own mobile applications. It is revealed that e-commerce enterprises should accumulate available information, analyze the frequency, place, time, and preferred channel of purchases, and form a point-based personalized offer. It is determined that digital transformation entails not only investment in new technologies and their subsequent implementation, but also the transformation of the product offered by the company in the market.